OPTIMALISASI GOOGLE MAPS UNTUK UMKM DI DESA BURANGKENG DALAM PENINGKATAN AKSESIBILITAS DAN PROMOSI - Arisandi, Akbar; Budiman, Rido; Rofieq, Ainur (An-Nizam, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in national economic growth, yet they continue to face various challenges, particularly in marketing and digital accessibility. One strategic effort to enhance MSME competitiveness is the optimization of Google Maps as a digitalization tool to expand market reach and improve business visibility. This community service program was implemented in Burangkeng Village with the objective of supporting MSMEs in the digitalization process by creating and optimizing their business locations on Google Maps. The program employed a door-to-door approach, in which students conducted direct socialization and training for MSME owners on how to register their businesses on Google My Business, update business information, and utilize Google Maps features to attract potential customers. The primary challenges encountered included limited technological knowledge among MSME owners and restricted internet access in certain areas. To address these issues, intensive mentoring and direct consultations were provided, enabling business owners to operate digital features independently. The outcomes of this program indicate improved MSME accessibility, expanded market reach, and enhanced adaptability of business owners to technological advancements. This program is expected to contribute to sustainable business development and strengthen local economic resilience.